Classification of several Yamato-75 chondrites (III) - Miura, Yasunori; Matsumoto, Yukio (1981)
P(論文) All the chondrites from the Yamato-75108 to -75257 have been considered to be originally one single body of meteorite which was broken into many fragments during its passage through the atmosphere. An electron microprobe analyzer was used to determine the chemical compositions of olivines and orthopyroxenes in five chondrites, i.e. Yamato-75135,93,-75136,93,-75140,50,-75140,51 and -75146,91. These chondrites are classified on the basis of textural characteristics of chondrule, matrix, igneous glass and secondary feldspar, and on the compositions of olivines and orthopyroxenes. The experimental results show that the chondrites are tentatively assigned to L group and petrologic type 4-5. These chondrites were possibly one single meteorite originally, together with eleven chondrites reported by MATSUMOTO et al. (Mem. Natl Inst. Polar Res., Spec. Issue, 12,72,1979), and MATSUMOTO and HAYASHI (Ibid, 17,21,1980). An unclassified chondrite, Yamato-75271,91,which was found at 5km south of the area where the chondrites Yamato-75108 to -75257 were collected, is determined to be of L group and petrologic type 4-5 based on the same analytical method as the above five chondrites. The chemical compositions of plagioclases in these six chondrites show a wide variation from oligoclase to andesine. departmental bulletin paper